The limits of power : the end of American exceptionalism - Bacevich, Andrew J. (New York : Metropolitan Books/Henry Holt and Company, 2009)
The Limits of Power identifies a profound triple crisis facing America: the economy, in remarkable disarray, can no longer be fixed by relying on expansion abroad; the government, transformed by an imperial presidency, is a democracy in form only; U.S. involvement in endless wars, driven by a deep infatuation with military power, has been a catastrophe for the body politic. These pressing problems threaten all of us, Republicans and Democrats. If the nation is to solve its predicament, it will need the revival of a distinctly American approach: the neglected tradition of realism. Andrew J. Bacevich, uniquely respected across the political spectrum, offers a historical perspective on the illusions that have governed American policy since 1945. The realism he proposes includes respect for power and its limits; sensitivity to unintended consequences; aversion to claims of exceptionalism; skepticism of easy solutions, especially those involving force; and a conviction that the books will have to balance. Only a return to such principles, Bacevich argues, can provide common ground for fixing America's urgent problems before the damage becomes irreparable.--From publisher description.
Includes bibliographical references and index.
Keywords: Power (Social sciences) -- United States; United States -- Politics and government; United States -- Politics and government -- 2001-2009.